The locus of linguistic variation - Lignos, Constantine; MacKenzie, Laurel; Tamminga, Meredith (Benjamins current topics,, 2018)
"This volume explores how the patterning of surface variation can shed light on the grammatical representation of variable phenomena. The authors explore variation in several domains, addressing intra- and inter-dialectal patterns, using diverse sources of data including corpora of naturally-occurring speech and judgment studies, and drawing on lesser-studied varieties of familiar languages, such as Northwest British Englishes and varieties of Canadian French. Ultimately, the contributions serve to expand our understanding of the nature of the mental representations and abstract processes required to support variation in language"--